Pengaruh Beberapa Kombinasi Media Tanam Organik Arang Sekam, Pupuk Kandang Kotoran Sapi, Arang Serbuk Sabut Kelapa Dan Tanah Terhadap Pertumbuhan Dan Hasil Tanaman Terung (Solanum Melongena L.) - Antonus Suban Hali; Albina Bare Telan (Research and Community Service Unit, Politeknik Kesehatan Kemenkes Kupang, 2018)
The purpose of this study was to determine the effect of the combination treatment of several organic growing media such as husk charcoal, manure of cow manure, coarse coir charcoal on the growth and yield of eggplant plants and to find out which combination treatments between planting media can produce the best eggplant. This study was designed with an environmental design in the form of a completely randomized design (CRD) consisting of 8 treatments and 3 replications. The variables observed included plant height, number of leaves and fruit weight. Observation data were analyzed using analysis of variance and Duncan's follow-up test at 5% level. The results of the analysis showed that the combination treatment of organizing media gave a very significant effect on the height increase of eggplant plants at 4 MST, 6 MST, 8 MST and 10 MST, and the number of leaves and a significant effect on the number of fruit. The treatment of the combination of organic planting media that gave the best growth and yields of eggplant was in the P8 treatment with a combination of soil treatment: rice husk charcoal: cow manure: coconut fiber charcoal with a ratio of 1:1:1:1; in P7 treatment with combination soil treatment: cow manure: 1:1:1 coconut husk charcoal; and P3 treatment with a combination of treatments between soil: 1:1 cow manure.